Preface - Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science; Vol 21 No 1 (2014), 2024)
This special issue of CAMES is devoted to eight research papers, selected from 30 papers presented at the 3rd International Symposium on Inverse Problems of Mechanics of Structures and Materials. The Symposium, called an IMP 2013 in short, was held in Rzeszów – Baranów Sandomierski, Poland on 24–27 April, 2013. It was a continuation of two previous symposia IPM 2009 and IPM 2011, organized in Łańcut and Sieniawa, Poland.